Learning from Livelihood Outcome of Social Safety Net Policy to Eradicate Poverty Amongst Fisherman Community in Surabaya, Indonesia - Dewi Casmiwati; Wildan Taufik Rahardja; Suprayitno P. Dayu; Aliyu Dawuha Abdullahi (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2026)
The fishermen in Kalanganyar, Sidoarjo Regency are mostly in poor condition, as seen from their income, education, and settlements. Therefore, Kalanganyar government provides assistance to them, in the form of Social Safety Net (SSN). The purpose of this study is to analyze the livelihood outcomes of SSN on fishermen's lives. The method used is qualitative with primary and secondary data. The data analysis technique used is thematic analysis. The framework in this study adopts the thoughts of Moser (1998), World Bank (2014), and Devereux (2000) regarding livelihood outcomes. The results of the study show that SSN have helped fishermen improve their lives by increasing educational security for beneficiary children and food security. However, there are some problems such as the village apparatus being unable to determine beneficiaries due to data coming from the central government, uncertain timing of assistance, jealously amongst the community over who receives assistance, and an a priori assumption of assistance from the apparatus. Therefore, the study recommends that village officials re-check the data of beneficiaries and submit it to the District Social Service for revision. Additionally, conducting socialization about the SSN program would lead to better understanding among the community.